Diversity analysis of Populus euphratica endophytic bacteria in Tarim River Basin, China - Gang Cheng; Yan Cheng; Erkin Rahman (PeerJ, 2023)
The bacterial diversity in Populus euphratica stem storage liquid samples grown in Shaya County and Yuli County of the Tarim River Basin was investigated. A culture-dependent (dilution spread plate method) and culture-independent method (PCR-RFLP technique) were used to identify the endophytic bacteria community structure and composition in P. euphratica in Tarim River Basin. Sixty-six bacterial strains were isolated from P. euphratica stem storage liquid samples on three agar media. The 16S rDNA gene was amplified and sequenced using bacterial universal primers. Phylogenetic analysis showed that the 66 strains belonged to three phyla (Firmicutes, Actinomycetes, and Gamma-Proteobacteria) and included 16 genera and 29 species. Among them, Pseudomonas (27.27%) and Bacillus (19.69%) were the dominant isolates. CGM-17 was a potentially new species of Pantoea. Restriction fragment length polymorphism of 16S rDNA gene amplified by polymerase chain reaction (PCR-RFLP) revealed 48 operational taxonomic units (OTUs). Phylogenetic analysis indicated that the 48 OTUs belonged to Firmicutes, Actinobacteria, Proteobacteria (α-, β-, γ-subgroup), Bacteroidetes, and Verrucomicrobia. Gamma-Proteobacteria was the dominant group, similarly to the culture-dependent method, accounting for 53% of the entire bacterial clone library. Our results indicate that P. euphratica endophytic bacteria diversity in the Tarim River Basin was rich, and the resources of endophytic bacteria were high. They provide valuable reference data and species resources for screening indigenous and functional strains of endophytic bacteria in P. euphratica.